Design and Characterization of Diclofenac Sodium Microbeads By Ionotropic Gelation Technique - P. S.GOUDANAVAR; R.S.BAGALI, CHANDRASHEKHARA.S; S. M.PATIL (International Journal of Pharma and Bio Sciences, 2010)
Sustained release oral product namely microbeads for Diclofenac sodium prepared by ionotropic gelation technique using Sodium alginate alone and combination with Hydroxypropyl methyl cellulose, Chitosan, Pectin as release rate modifiers, and investigated for flow behavior, particle size, swelling properties, surface study by SEM, and in vitro drug release potential. While increase in the concentration of sodium alginate and other polymer dispersions increased sphericity, size distribution, mean particle size. Drug entrapment efficiency approached nearly 95%. Increasing calcium chloride concentration decreases the mean diameter of the microbeads, no appreciable change in morphology, and drug release behaviors. In vitro drug release was dependent on the pH of the medium and concentration of polymer dispersions. Among the nine formulation batches F5, F7 and F9 were found to show optimum sustained effect. The mechanism of drug release from the microbeads was found to be followed super case-II transport.